ACCOUNTING INFORMATION SYSTEMS INCREASE MSMEs PERFORMANCE - Nicholas Renaldo; Suharti; Andi; Novita Yulia Putri; Cecilia (Journal of Applied Business and Technology, 2021)
Micro, Small, and Medium Enterprises (MSMEs) are businesses that must be controlled by a community group or family. Micro, Small, and Medium Enterprises (MSMEs) SMEs have a strategic role in national economic development because apart from contributing to national economic growth they can also provide a large workforce. The inability to present the accounting and information used is one of the weaknesses of the management side. This study focuses on the effect of accounting information systems on performance in Micro, Small, and Medium Enterprises (UMKM). Company performance is the condition of the company which is analyzed using financial analysis tools so that good and bad conditions can be produced that reflect the company's financial performance in a certain period. The population in this study are the owners of Micro, Small, and Medium Enterprises spread across the city of Pekanbaru with a total of 1,201 units. The sample of this research is 100 respondents who own Micro, Small, and Medium Enterprises (MSMEs). Sampling uses the convenience sampling technique, a convenience sample is formed when we select elements from a population on the basis of what elements are easily obtained by owners of Micro, Small, and Medium Enterprises (MSMEs). The analytical tool used in this study is multiple linear regression. The results of this study indicate that the accounting information system variables affect the performance variables of Micro, Small, and Medium Enterprises (MSMEs) in the Pekanbaru city area.